PENINGKATAN HASIL BELAJAR DAN KEMAMPUAN BERFIKIR MELALUI HYBRID LEARNING PADA SISWA KELAS IV PADA MATERI KPK DAN FPB DI UPT SPF SD NEGERI 101801 KEDAI DURIAN - Apriliyanti, Nova; Safrida Napitupulu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine teacher activities in implementing the Hybrid Learning model on the KPK and FPB material, to determine student activities in implementing the Hybrid Learning model on the KPK and FPB material and to determine the use of the Hybrid Learning learning model can improve learning outcomes and students' thinking skills in class on the KPK and FPB material in class IV UPT SPF SD Negeri 101801 Kedai Durian, the hybrid learning model is a combination of face-to-face learning with online learning or e-learning. The form of this research is classroom action research (PTK) which is carried out in 3 cycles. Each cycle consists of four stages, namely the planning, implementation, observation, and reflection stages. The research subjects were class IV UPT SPF SD NEGERI 101801, which consisted of 29 students. The data collection techniques used were observation, interviews, and documentation. The validity of the data used was source triangulation and technique triangulation. The data analysis used was interactive analysis. The results of this study can be concluded that through the hybrid learning model, it can improve the learning outcomes of mathematics students in the FPB-KPK material at IV UPT SPF SD NEGERI 101801.